Morphological Variation of the Left Lung: Presence of an Accessory Lobe - Junqueira, José Ari Gualberto [UNESP]; Watanabe, Luciane Naomi Oguma; Ferreira-Pileggi, Beatriz Carmona; Rossi, Ana Cláudia; Botacin, Paulo Roberto [UNESP]; Prado, Felippe Bevilacqua; Freire, Alexandre Rodrigues (My University, 2023)
Introduction: the lungs are organs that supply gas exchange, existing in both sides of the human body. The left lung has an oblique fissure separating the superior lobe from the inferior lobe, whereas the right lung has horizontal and oblique fissures separating it into superior, middle and inferior lobes. Anatomical variations may occur in the lungs and the left lung can have three lobes and the right lung can have four or only two lobes. The aim of this study was to report a case of a cadaver with an anatomic variation of the left lung with an accessory lobe. Case report: during a routine Anatomy dissection of a female adult cadaver, a three-lobed left lung was found. The left lung had an upper lobe, a middle lobe and a lower lobe. The upper and middle lobes were separated by a complete horizontal fissure. The middle and lower lobes were separated by a complete fissure with an oblique appearance (inferior to superior direction). Conclusion: pneumatologists and surgeons must be aware of the lung anatomical variations. This knowledge can make the surgeon more prepared for adverse situations and may decrease the occurrence of intraoperative difficulties and post-surgery complications when performing lung transplantation or surgical management of lung pathology, lobectomies and segmental resection and for interpreting computed tomography scans.
Keywords: Accessory lung; Anatomic variation; Clinical Anatomy; Lung Transplantation; Macroscopic human anatomy